LAYANAN KHUSUS PESERTA DIDIK (KESISWAAN) - Adi Putra (El-Idare, 2016)
Learners are a core component of educational activities. The era of competition among educational institutions so tight as it is today, the school must strive in earnest to get learners. There is even a chairman of the foundation of education that says that seek learners is much more difficult than looking for a new teacher. Mananjemen student not only shaped data recording learners, but covers broader aspects yange operationally to assist the efforts of growth and development of learners through the process of education in schools. As a special service of learners includes guidance and counseling services, library services, a cafeteria service / kafetarian, health services, transformation services schools, service hostel, and services extracurricular, laboratory services, and security. A special service was held in the school with a view to facilitate the implementation of teaching in order to accomplish the goals of education in schools. Special service management is a process of providing services to the needs of learners to support learning activities for educational purposes can be achieved effectively and efficiently.